2008
DOI: 10.1016/j.biocel.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Sulfotransferase 4A1

Abstract: In this review, we highlight the physical and enzymatic properties of the novel human sulfotransferase, SULT4A1. The gene is most highly expressed in selective regions of the brain, although work to date has failed to identify any specific endogenous substrate for the enzyme. SULT4A1 shares low homology with other human sulfotransferases. Nevertheless, it is highly conserved between species. Despite the low homology, it is structurally very similar to other cytosolic sulfotransferases with a conserved substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Another interesting and perplexing discovery was the upregulation of SULT4A1 mRNA in NASH (not fatty/cirrhosis). SULT4A1 is almost exclusively expressed in brain, and is very highly conserved among species although it has no known endogenous ligand (Gamage et al, 2006;Minchin et al, 2008). One study has shown an elevation in hepatic SULT4A1 expression after ventromedial hypothalamic lesions, which are known to cause significant disruptions in metabolic homeostasis manifesting as obesity and hyperinsulinemia similar to that seen in metabolic syndrome, an accompanying feature of NAFLD (King, 2006;Kiba et al, 2009;McCullough, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting and perplexing discovery was the upregulation of SULT4A1 mRNA in NASH (not fatty/cirrhosis). SULT4A1 is almost exclusively expressed in brain, and is very highly conserved among species although it has no known endogenous ligand (Gamage et al, 2006;Minchin et al, 2008). One study has shown an elevation in hepatic SULT4A1 expression after ventromedial hypothalamic lesions, which are known to cause significant disruptions in metabolic homeostasis manifesting as obesity and hyperinsulinemia similar to that seen in metabolic syndrome, an accompanying feature of NAFLD (King, 2006;Kiba et al, 2009;McCullough, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…SULT4A1 mRNA can exist as two different transcripts depending on the splicing of an aberrant exon between exons 6 and 7 (Minchin et al, 2008). In Neuro2a cells, the variant transcript was the major transcript detected, whereas in the mouse primary neurons, only the wild-type transcript was detected (Fig.…”
Section: Overexpression Of Creb and Atf-2 Increases Sult4a1mentioning
confidence: 99%
“…which would produce a truncated protein (Minchin et al, 2008). The truncated protein may lack the antibody binding site(s), or the resultant protein may be rapidly degraded.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…A number of independent clones were identified, and their binding to SULT4A1 was confirmed. One set of clones was SULT4A1 itself, which is expected given that the cytosolic sulfotransferases, including SULT4A1, contain a dimerization site in their C termini (Minchin et al, 2008). A second set of clones contained the complete open-reading frame for Pin1, a ubiquitously expressed protein that belongs to the parvulin family of peptidyl-prolyl cis-trans isomerases.…”
Section: Resultsmentioning
confidence: 99%